The Effect of Audio Visual Media on Students’ Reading Comprehension - nurmahyuni asrul; Irma Khoirot Daulay; Dwi Suci Amaniarsih (Universitas Suryakancana, 2020)
Audio Visual Media has been thoroughly used by teachers and learners and has become an interesting teaching tool for teaching-learning process. One of the audio-visual aid of processes used in this study was video. The objective of this research was to find out the effect of Audio Visual Media on students’ reading comprehension. Is there any significant effect on students’ reading comprehension toward audio visual media become the problem of this research. To clarify this question, the sample was divided into two groups, control group and experimental group. The total of the sample was 50 students. The experimental group was given a treatment by using Audio Visual Media while the control group was given a treatment by using conventional method. Multiple choice test consisted 25 items was an instrument in this study. It was given before and after the treatment to measure the students’ reading comprehension. Both of groups were given the same material. Based on the result, the students who were given a treatment by using audio visual media got better results compare to the students who were given a treatment without audio visual media with the value of t-table = 2,0000 < t-observed = 6,1851. So, the null hypothesis (Ho) is successfully rejected. It could be conclude that the audio visual media significantly affects on students’ reading comprehension.